2008
DOI: 10.1017/s0022215107008560
|View full text |Cite
|
Sign up to set email alerts
|

Is there an association between blood group O and epistaxis?

Abstract: Blood group O appears over-represented in Caucasian patients admitted with epistaxis, compared with the control population, raising the possibility that blood group O is a risk factor for epistaxis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 8 publications
2
24
0
Order By: Relevance
“…The logical extension of these associations to correlations with ABO blood type and thrombo-embolic phenomena has also been demonstrated [22]. ABO phenotype has also been shown to correlate with haemorrhagic pathologies, including cerebral haemorrhage [23] and epistaxis [24]. Prior to our series, ABO phenotype was not specifically associated with post-operative haemorrhage.…”
Section: Type-o Blood and Coagulationsupporting
confidence: 55%
“…The logical extension of these associations to correlations with ABO blood type and thrombo-embolic phenomena has also been demonstrated [22]. ABO phenotype has also been shown to correlate with haemorrhagic pathologies, including cerebral haemorrhage [23] and epistaxis [24]. Prior to our series, ABO phenotype was not specifically associated with post-operative haemorrhage.…”
Section: Type-o Blood and Coagulationsupporting
confidence: 55%
“…Reddy et al [1] found in their study that among Caucasian epistaxis patients 50.4 patients were blood group O but among control groups this was 45.10%.…”
Section: Discussionmentioning
confidence: 88%
“…Earlier it has been reported that blood group O was over represented in Caucasian patients admitted with epistaxis, compared with the Caucasian population in general [1] . One study revealed that bleeding time was significantly longer in people with blood group O than people with non-O blood group and this could not be correlated with sex ratio, platelet count or hematocrit [2] .…”
Section: Introductionmentioning
confidence: 95%
“…21 (Table S1), which has recently been found in the Vienna Bleeding Biobank (VBB) to be associated with the diagnosis of a bleeding disorder and previously been described in association with bleeding from a range of causes , . [22][23][24][25] TxA and desmopressin and rarely platelet transfusion were successful in more than 90% of cases at reducing bleeding complications when given as haemostastic prophylaxis preprocedure; 16 of 69 procedures were high bleeding risk and no abnormal bleeding was observed ( 11 The variability we describe in management with platelets, TXA and desmopressin reflects the uncertainty of managing UBD given the lack of any clinical trials. Many patients, prior to diagnosis, experienced postoperative, postdental or PPH; 75%, 84% and 63%, respectively, for patients exposed to each risk.…”
Section: Discussionmentioning
confidence: 94%